The Bambui Health and Aging Study (BHAS): factors associated with the treatment of hypertension in older adults in the community Projeto Bambuí: fatores associados ao tratamento da hipertensão arterial entre idosos na comunidade - Josélia Oliveira Araújo Firmo; Sandhi Maria Barreto; Maria Fernanda Lima-Costa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
The objective of this study was to investigate the factors associated with the treatment of hypertension among older adults living in the community. All residents (n = 1,742) of Bambuí, Minas Gerais State, Brazil (15,000 inhabitants) aged ³ 60 years were selected, and 1494 (85.8%) were interviewed and examined. Of these, 919 (61.5%) were hypertensive, 704 were aware of their condition (study population), and 578 were under treatment. Only 38.8% of the individuals under treatment presented controlled systolic and diastolic pressures (< 140 and < 90mmHg, respectively). Independent associations with treatment of hypertension were found for, in decreasing order of magnitude: less time elapsed since the last blood pressure measurement, greater number of physician visits in the past 12 months, higher body mass index, female gender, history of coronary disease, changes in diet due to arterial hypertension, and higher family income. Our results show that the factors most strongly associated with treatment of hypertension (use of health services) could be modified through adequate health policies for older adults. O objetivo deste estudo foi determinar os fatores associados ao tratamento da hipertensão entre idosos residentes na comunidade. Todos os residentes (n = 1.742) na cidade de Bambuí (15 mil habitantes) com ³ 60 anos foram selecionados; 1.494 (85,8%) participaram do estudo. Desses, 919 (61,5%) eram hipertensos; 704 sabiam ser hipertensos (população estudada), 578 estavam sendo tratados. Entre os tratados, somente 38,8%, apresentavam pressão sistólica e diastólica controlada (< 140 e < 90mmHg, respectivamente). Associações independentes com o tratamento da hipertensão arterial foram encontradas, em ordem decrescente de magnitude, para menor tempo decorrido após a última medida de pressão arterial, maior número de consultas médicas nos últimos 12 meses, maiores índices de massa corporal, sexo feminino, história de doença coronariana, mudanças na alimentação por causa da hipertensão arterial e maior renda familiar. Nossos resultados mostram que os fatores mais fortemente associados com o tratamento da pressão arterial (uso de serviços de saúde), poderiam ser modificados por meio de políticas de saúde adequadas para a população idosa.